Atmospheric blocking and its relation to jet changes in a future climate - de Vries, H; Woollings, T; Anstey, J; Haarsma, R; Hazeleger, W (2013)
The future changes of atmospheric blocking over the Euro-Atlantic sector, diagnosed from an ensemble of 17 global-climate simulations obtained with the ECHAM5/MPI-OM model, are shown to be largely explainable from the change of the 500 hPa mean zonal circulation and its variance. The reduction of the blocking frequency over the Atlantic and the increased frequency of easterly upper-level flow poleward of 60°N are well explained by the changes of mean zonal circulation. In winter and autumn an additional downstream shift of the frequency maximum is simulated. This is also seen in a subset of the CMIP5 models with RCP8.5. To explain this downstream shift requires the inclusion of the changing variance. It is suggested that the increased downstream variance is caused by the stronger, more eastward extending future jet, which promotes Rossby wave breaking and blocking to occur further downstream. The same relation between jet-strength and central-blocking longitude is found in the variability of the current climate. © 2013 Springer-Verlag Berlin Heidelberg.